IMPLEMENTASI PERATURAN DAERAH NO 7 TAHUN 2013 TENTANG PENGELOLAAN SAMPAH TERHADAP PERAN DINAS LINGKUNGAN HIDUP PEMUKIMAN DAN KEBERSIHAN KABUPATEN PINRANG DALAM PENANGGULANGAN LIMBAH DOMESTIK - Guliling, Satrio; Hamzah, Hartono; Hidayat, Asrul (Datuk Sulaiman Law Review (DaLRev), 2024)
This study aims to describe the implementation of Regional Regulation No. 7 of 2013 on Waste Management in Pinrang Regency and to describe the role of the Environmental, Housing, and Cleanliness Agency in managing domestic waste in Pinrang Regency. The findings of this study show that waste management has been carried out through several concrete steps, but it has not yet been fully optimal due to the accumulation of waste in areas with high activity. The role of the Environmental, Housing, and Cleanliness Agency in addressing domestic waste in the urban areas of Pinrang Regency includes the planning and implementation of waste management programs, including waste collection, sorting, and processing, which have not been fully effective. This highlights the need for improved supervision and public education on the importance of waste sorting and management.